Descriptive Patterns of Instruction, Technology Use, and Creative Thinking in Secondary Physics Education - Putra, Nurhamdin; Akmam, Akmam (UIN Fatmawati Sukarno Bengkulu, 2026)
Persistent challenges in secondary physics education include uneven instructional implementation, limited pedagogical use of digital technology, and modest development of higher-order competencies such as creative thinking. While prior studies have often examined these dimensions separately, integrated descriptive evidence across authentic school contexts remains limited, particularly in resource-diverse educational environments. This study aims to descriptively analyze the alignment among instructional practices, technology-supported learning facilities, students’ affective characteristics, and creative thinking–oriented physics achievement across three public senior high schools in Indonesia. A quantitative descriptive design was employed involving 102 students. Data were collected using Likert-scale questionnaires on learning implementation and affective characteristics, a binary instrument on access to digital learning facilities, and a multiple-choice physics achievement test targeting higher-order conceptual understanding in heat and thermal expansion. Descriptive statistical analysis revealed relatively consistent instructional structures across schools, yet substantial variation in practicum activities, technology utilization, and facility access. Although students demonstrated moderate motivation and positive attitudes toward physics, creative thinking achievement remained below half of the maximum score in all schools, indicating a misalignment between instructional conditions and higher-order learning outcomes. These findings provide baseline empirical evidence highlighting the need for stronger alignment among pedagogy, technological integration, and targeted competencies to support meaningful physics learning in resource-varying secondary education contexts.